How to increase the awareness of in-app mobile banner ads: exploring the roles of banner location, application type and orientation - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2018)
In-app mobile banner ads appear as promising communication tools and are increasing in popularity due to spread and use of mobile technologies in consumers' life. On the other hand, the effectiveness of these ads is under scrutiny due to banner blindness and habituation. Till now, there have been a limited number of studies to explore the dynamics of crafting an effective in-app banner ad. This study aims to fill this gap in research by applying an experimental design to examine the effects of banner location, application type and application orientation. The results of the study show that all the factors had an effect on recall of in-app mobile advertising. Users recalled the banner and its contents better when the context was landscape game and the banner was located at the top. In all contexts, recall was higher when the banner was located at the top of the application. The results of this study contribute to the extant knowledge on the literature and also put forth significant implications for the brand owners who want to use in-app mobile ads in the future.
Keywords: digital ads; in-app advertising; mobile ads; mobile applications; mobile banner; IMPACT